The role of social counseling in facing the problems of widows and divorcees - A field study on the beneficiaries of Organization Girl albadayie - Saudi Arabia (1444-2023) - Alnwaiser, Feda Mohammed (Journal of Humanities & Social Sciences, 2024)
Divorced and widowed women face many challenges and difficulties as a result of losing her husband, which made her need to overcome these problems, and she may not be able to overcome them alone.this study aimed to find out the role of social counseling in facing the problems of widows and divorcees by identifying the most prominent social, educational and psychological problems facing widowed or divorced women and to know the role of a social worker in helping widowed or divorced women to face them. The study was based on the Social Survey Methodology and on the questionnaire as a tool for collecting data from the vocabulary of the sample, which amounted to(78) a widow and a divorcee in the Bidaya governorate from the beneficiaries of the Bidaya girl Charity Association. The study found several results are: that woman is widowed or divorced faces many social problems and psychological, which most notably the lack of their ability to face the problems themselves by(39, 7%) the difficulty of caring and raising of children by(24,4%), and the social worker helps widows and divorced in re-adapting to social changes and guide them towards effective ways to communicate with children by(55, 1%). The recommendations of the study came as follows: the need to benefit from researchers and social workers and employ them in various community institutions that deal with widows and divorcees and use them in providing social consultations and work to establish many social research and scientific studies to find out the renewed needs and emerging problems facing the category of widows and divorcees.the study recommends various community institutions from schools and universities in their role in educating individuals about the importance of the role of a social worker in helping to solve social problems. the study recommends the category of widows and divorcees the importance of resorting to a social worker in case of problems, whether related to the widow herself or her children.
Keywords: Social counseling; problems; widows; divorcees